A comparative study of surgical site infection after single dose of preoperative antimicrobial prophylaxis versus multiple doses of antimicrobials in clean and clean contaminated abdominal surgeries - Vala, Haresh; Vaja, Maulik A.; Gohil, Ajit B. (International Surgery Journal, 2020)
Background: The advent of antimicrobial therapy has offered an important adjuvant to the prevention of surgical infection. In spite of vast accumulation of research and review published there are still conflicting views. Some study shows multiple doses require for the eradication of microorganisms in the wound. While numerous authors have reported that single dose of an appropriate antibiotic is effective, but there has been no direct comparison of one dose against three doses regimens. Objective was to study about effect and safety of single dose of antibiotic against routine multiple dose regimens in clean and clean-contaminated abdominal surgeries. Methods: Patients recruited in the study according to specific inclusion and exclusion criteria. The participants were divided in two groups: group I and group II. Group I was given single dose of injection cefotaxime. While another group was given 5 days course of injection cefotaxime and injection amikacin or injection ciprofloxacin and injection metronidazole. Postoperative wound was assessed by Southampton wound grading system. Results: The rate of wound infection on 3rd day was for 16.30% for group I and 13.82% for group II. The infection rate decrease on 7th post-operative day and it was 13.04% for group I and 11.7% for group II. Conclusions: Long course of antibiotic as prophylaxis has no added advantage. Good operative technique plays a major role in preventing infections. Single dose antibiotic regimen has comparable infection rate for clean surgical cases and it saves lot of money in this era of cost containment.